2016
DOI: 10.1002/2016gl070145
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of stress inversion of focal mechanisms to pore pressure changes

Abstract: We investigate the sensitivity of stress inversion from focal mechanisms to pore pressure changes. Synthetic tests reveal that pore pressure variations can cause apparent changes in the retrieved stress ratio R relating the magnitude of the intermediate principal stress with respect to the maximum and minimum principal stresses. Pore pressure and retrieved R are negatively correlated when R is low (R < 0.6). The spurious variations in retrieved R are suppressed when R > 0.6. This observation is independent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…At the selected location at The Geysers geothermal field, local stresses were found to change, mainly related to fluid injection, which directly affects thermal stresses and pore fluid pressure in the reservoir. On a longer time scale, the stress ratio R was observed to slightly decrease [ Kwiatek et al ., ; Martínez‐Garzón et al ., ]. Within shorter time periods, Martínez‐Garzón et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the selected location at The Geysers geothermal field, local stresses were found to change, mainly related to fluid injection, which directly affects thermal stresses and pore fluid pressure in the reservoir. On a longer time scale, the stress ratio R was observed to slightly decrease [ Kwiatek et al ., ; Martínez‐Garzón et al ., ]. Within shorter time periods, Martínez‐Garzón et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a number of short‐ and long‐term transients in seismomechanical characteristics were identified that are related to changing injection rates. These include distance of seismicity from injection well, different faulting styles, b values from Gutenberg‐Richter distributions, and stress ratio R from stress tensor inversion [ Martínez‐Garzón et al ., ; Kwiatek et al ., ; Martínez‐Garzón et al ., ]. Importantly, the seismicity from this cluster has revealed significant changes of the stress field orientation of approximately ≈ 15–20° during periods of high injection rates [ Martínez‐Garzón et al ., ].…”
Section: Site Characteristics Seismicity Data and Hydraulic Parametersmentioning
confidence: 99%
“…The crustal region beneath the Higher Himalaya shows a nearly N‐S oriented σ 1 with a plunge of 33° and near horizontally plunging E‐W oriented σ 3 with an acceptable misfit angle of 45° (Figure b). The above segments indicate a transpressive stress regime, as our stress inversion results show a relative vertical orientation of σ 2 with respect to σ 1 and σ 3 and a lesser R value (<0.25; e.g., Martínez‐Garzón et al, ). The upper mantle region beneath the Higher Himalaya shows a NNW‐SSE oriented σ 1 with a plunge of 36° and near horizontally plunging ENE‐WSW oriented σ 3 (Figure c).…”
Section: Resultsmentioning
confidence: 64%
“…with an acceptable misfit angle of 45 •(Figure 6b). The above segments indicate a transpressive stress regime, as our stress inversion results show a relative vertical orientation of 2 with respect to 1 and 3 and a lesser R value (<0.25; e.g.,Martínez-Garzón et al, 2016b). The upper mantle region beneath the Higher Himalaya shows a NNW-SSE oriented 1 with a plunge of 36 • and near horizontally plunging ENE-WSW…”
mentioning
confidence: 99%
“…In order to analyze tectonic stress in the focal zone we use the public‐open Matlab code STRESSINVERSE (http://www.ig.cas.cz/stress-inverse) for a joint inversion of focal mechanisms for stress and fault orientations developed by Vavryčuk (). The method is based on the Michael's inversion for stress (Michael, , ) that is run in iterations and utilizes the fault instability criterion (Martínez‐Garzón et al, ; Vavryčuk et al, ) for discriminating which of two nodal planes is the fault plane. The method is fast and robust and provides uncertainty limits of results.…”
Section: Tectonic Stressmentioning
confidence: 99%